Optimizing Warehouse Management in Footwear Commercial Companies: A Case Study on Lean-BPM - Acevedo Aybar, C. E. (2024)
The article presents a case study on optimizing warehouse management in a footwear commercial company using the Lean-BPM methodology. The company experienced low performance in fulfilling complete and on-time orders, resulting in customer dissatisfaction. The proposed model includes tools such as 5S, Multicriteria ABC, Kardex, standard work, and BPM. The implementation of the model resulted in a significant improvement in the On Time, In Full index (OTIF). The study demonstrates that the proposed model can improve warehouse management efficiency in similar companies, which is crucial for business competitiveness and customer satisfaction. The worldwide crisis has created issues for Peru’s footwear industry, which is crucial to the country’s economy. These challenges include decreased output and exports, as well as the susceptibility of small and medium-sized businesses. Adopting new tools and technology, fostering training initiatives, and enhancing corporate management are critical to the sector’s expansion. Inadequate warehousing, physical distribution and inventory management are common causes of customer dissatisfaction in the retail industry. The proposed model addresses these issues by standardizing processes, improving product knowledge, and reducing production errors. The study highlights the importance of implementing effective warehouse management strategies to meet the demands of speed and correct delivery in the competitive business environment.